1999
DOI: 10.1088/0741-3335/41/3a/045
|View full text |Cite
|
Sign up to set email alerts
|

Alfvénic turbulence associated with density and temperature filaments

Abstract: Abstract.A systematic laboratory study of controlled density and temperature filaments having transverse scale length comparable to the electron skin-depth has been performed in the large plasma device (LAPD) at UCLA. It is found that large amplitude shear Alfvén waves develop spontaneously and are localized within the filaments. As the plasma conditions change (e.g., lowering the plasma beta parameter or increasing the heating power) the highly coherent eigenmodes develop into broad band Alfvénic turbulence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In the solar wind region and over a wide range of heliospheric distances, the quantity ∣ δB y 0 ∣/ B 0 tends to be small (≈5%) [ Matthaeus and Goldstein , 1982; Roberts et al , 1987]. Morales et al [1999] studied density and temperature filaments in laboratory at fluctuating levels of ∣ δB ⊥ ∣/ B 0 ≈ 10 −3 , under conditions of relevance to the auroral ionosphere. The characteristic scales of the filament size for all the three regions are of the order of 2 ρ s (at e −1 of the intensity peak) and the separation of the filaments is of the order of 10 3 ρ s for lower values of g .…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the solar wind region and over a wide range of heliospheric distances, the quantity ∣ δB y 0 ∣/ B 0 tends to be small (≈5%) [ Matthaeus and Goldstein , 1982; Roberts et al , 1987]. Morales et al [1999] studied density and temperature filaments in laboratory at fluctuating levels of ∣ δB ⊥ ∣/ B 0 ≈ 10 −3 , under conditions of relevance to the auroral ionosphere. The characteristic scales of the filament size for all the three regions are of the order of 2 ρ s (at e −1 of the intensity peak) and the separation of the filaments is of the order of 10 3 ρ s for lower values of g .…”
Section: Simulation Resultsmentioning
confidence: 99%
“… Chmyrev et al [1988] found the perpendicular scale size of the filaments of Alfvén vortex tubes propagating transverse to the background magnetic field of the order of ρ s when β > m e / m i and λ e when β < m e / m i . Morales et al [1999] analyzed filamentary structures in laboratory nonthermal plasmas with transverse scale size of the order of λ e , spontaneously generating Alfvénic turbulence spatially localized to the filament region. In case of polar cusp, the scale size of the filament is 2 ρ s (= 20 km) in our result.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…For these typical parameters at ω/ω ci = 0.02 and k x ρ s = 0.001, the magnitudes of the fluctuations are |δB y0 |/B 0 = 0.003 and = 0.02. Morales et al (1999) studied density and temperature filaments in the laboratory at fluctuation levels of |δB ⊥ |/B 0 ≈ 10 −3 , under conditions of relevance to the auroral ionosphere. The observed filamentary structures of Figure 5 have the characteristic transverse scale size of the order of λ e (at e −1 of the intensity peak).…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The observed filamentary structures of Figure 5 have the characteristic transverse scale size of the order of λ e (at e −1 of the intensity peak). Morales et al (1999) analyzed filamentary structures in laboratory nonthermal plasmas with transverse scale size of the order of λ e , spontaneously generating Alfvénic turbulence spatially localized in the filament region.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation